Towards more sustainable patterns of urban development. (August 2019) - Marino, F P R; Lembo, F; Fanuele, V
Abstract: DETR, 1998, wrote in Planning for Sustainable Development. Towards Better Practice : " New settlements will enjoy a high quality of urban and landscape design. As well as integrated open space, there should be habitat areas, and environmental gains such as energy efficiency measures introduced in layouts and individual buildings "; but this claim is remained largely dissatisfied. There is a great interest (and large investments in research) for the smart city, which seeks to optimize the existing cities, while people go on to design urban developments with building typologies set ninety years ago by Modern Movement or little more. Urban Planning compares existing cities' models and asseverates that densification has positive role for sustainability, but do not turns enough to account passive typologies for heating and cooling, which can turn down near to zero power-consumption, and at the same time can raise urban environment quality. Famous settlements too, as Malmö or Vauban in Freiburg, has been built with building typologies conventional, after all; German passive Haus have generally two, three or four building fronts and in reality, are simply hyper-insulated traditional buildings, furnished with mechanical controlled ventilation. For an urban extension of Potenza, we have used for the urban planning the sustainability assessment categories of ITACA's Protocol, derivative from GB Tool of GBC, people normally use to assess ex-post sustainability of projects and of realized buildings. The result is a settlement in which pedestrian, cycle and public transport's network is fully integrated with adjacent urban areas; effective landscaping connects public and private green and kitchen-gardens/orchards are everywhere; buildings are made with new semi-underground typologies, nZEB and made with local, re-cyclable materials; rain water is collected, in-loco fito-depurated and reused; in-loco renewable energies (sun, earth, wind) satisfies remaining necessities.